OVERCOMING DORMANCY IN Coffea arábica SEEDS WITH DIFFERENT IMMERSION TIMES IN SODIUM HYPOCHLORITE - Eduarda Yasmin Nunes de Souza; Pablo Wenderson Ribeiro Coutinho; Danielle Acco Cadorin de Fraga; Fernando Roberto Cologni; Gabriel Matsuda; Liane Piacentini (Revista de Agricultura Neotropical)
Germination of coffee seeds (Coffea arabica L.) can take between 90 and 120 days, making the process slow and impacting production. This study evaluated the effect of sodium hypochlorite (NaClO) immersion time on dormancy breaking in seeds, aiming to optimize coffee crop management to improve productivity and quality. The experimental design was completely randomized in a 2 × 6 factorial scheme with four replications. The first factor was immersion in NaClO and H2O, while the second factor corresponded to the immersion time in each solution (03h, 06h, 09h, 12h, 15h, and 18h). The analyzed variables included germination percentage (G%), germination speed index (GSI), mean germination time (MGT), mean germination rate (MGR), as well as seedling length and dry (DM) and fresh mass. NaClO yielded better G%, GSI, and DM results, while immersion in H2O stood out for MGT, MGR, and root length. The results highlight the need to consider the effectiveness of dormancy breaking and its effects on early seedling development.